Digital Story Project: Using Technology to Foster Learners Speaking Skill - Wijayanti, Fitri (Politeknik Negeri Jember, 2020)
The availability of technologies for instructional purposes has grown rapidly. One of them is using a digital story to teach English for polytechnic students. Actually, it is not a new learning platform, but few teachers apply it in their own classroom especially in the Asian context where English is viewed as a foreign language. To fill this void, the researcher deployed digital storytelling which involved students in creating digital stories and voicing their experience orally. This article further explains the implementation of digital storytelling as a pedagogical language input to foster the students speaking skills which involved the first semester students in Basic English course. Besides, the students engage actively in describing their experiences and showing visual background, which was assisted by a technological application available. The practical implication of this project is that the EFL teachers are able to deploy digital storytelling in their classroom as a medium to bridge learners through meaningful context and social practices.